Some reflections on multilateral environmental agreements - Frank Stähler (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1994)
In an international setting, sovereignty of countries imposes serious problems on compliance and participation for a multilateral environmental agreement. This paper discusses both problems simultaneously in a three-country-setting. It employs a repeated-game-model and develops some basic conditions which agreements must meet. These conditions are applied on a specific model which allows only a subcoalition of two countries to join an agreement. However, this subcoalition is able to introduce transfer policies which initiate extra reductions of the outsider country. The paper shows that transfer policies may be based on a cost-inferior technology which makes non-compliance less attractive.
Keywords: 330; Umweltpolitik; Umweltabkommen; Internationaler Transfer; Spieltheorie; Theorie